Turning Toward Monitoring of Gaze Stability Exercises: The Utility of Wearable Sensors. Issue 4 (October 2020) - Loyd, Brian J.; Saviers-Steiger, Jane; Fangman, Annie; Ballard, Parker; Taylor, Carolyn; Schubert, Michael; Dibble, Lee
Abstract : Background and Purpose: Few tools are currently available to quantify gaze stability retraining exercises. This project examined the utility of a head-worn inertial measurement unit (IMU) to quantify head movement frequency, velocity, and amplitude during gaze stability exercises. Methods: Twenty-eight individuals with multiple sclerosis and complaints of dizziness or a history of falls were randomly assigned to either a strength and aerobic exercise (SAE) or gaze and postural stability (GPS) group. During a 6-week intervention, participants wore a head-mounted IMU 3 times (early, middle, and late). For aim 1, the frequency, mean peak velocity, and mean peak amplitude of head turns during equivalent duration components of group-specific exercises were compared using general linear models. For aim 2, the progression of treatment in the GPS group was examined using general linear regression models for each outcome. Results: Aim 1 revealed the GPS group demonstrated significantly greater velocity and amplitude head turns during treatment than the SAE group. The frequency of head turns did not significantly differ between the 2 groups. The aim 2 analyses demonstrated that the yaw and pitch frequency of head turns significantly increased during gaze stability exercises over the 6-week intervention. Velocity and amplitude of head turns during yaw and pitch gaze stability exercises did not significantly change. Discussion and Conclusions: A head-worn IMU during rehabilitation distinguished between groups. Furthermore, within the GPS group, the IMU quantified the progression of the frequency of head movements during gaze stability exercises over time. Video Abstract available for more insights from the authors (see the Video, Supplemental Digital Content 1, available at: http://links.lww.com/JNPT/A320 ). Abstract : Supplemental Digital Content is Available in the Text.